Teaching Journalism Literacy in Schools: The Role of Media Companies as Media Educators in Germany - Sengl, Michael (2023)
German journalism is facing major challenges including declining circulation, funding, trust, and political allegations of spreading disinformation. Increased media literacy in the population is one way to counter these issues and their implications. This especially applies to the sub-concept of journalism literacy, focusing on the ability to consume news critically and reflectively, thus enabling democratic participation. For media companies, promoting journalism literacy seems logical for economic and altruistic reasons. However, research on German initiatives is scarce. This article presents an explorative qualitative survey of experts from seven media companies offering journalistic media education projects in German schools, focusing on the initiatives’ content, structure, and motivation. Results show that initiatives primarily aim at students and teachers, offering mostly education on journalism (e.g., teaching material) and via journalism (e.g., journalistic co-production with students). While these projects mainly provide information on the respective medium and journalistic practices, dealing with disinformation is also a central goal. Most initiatives are motivated both extrinsically (e.g., reaching new audiences) and intrinsically (e.g., democratic responsibility). Despite sometimes insufficient resources and reluctant teachers, media companies see many opportunities in their initiatives: Gaining trust and creating resilience against disinformation are just two examples within the larger goal of enabling young people to be informed and opinionated members of a democratic society.